Anti-genotoxic and anti-oxidative effects of cladonia rangiformis extracts against aflatoxin B1in vitro - Kotan, Elif; Agar, Güleray; Alpsoy, Lokman; Aslan, Ali; Erman, Fazilet; Nardemir, Gokce (My University, 2013)
Aflatoxin B1 (AFB1), is a common human carcinogen causing genotoxicity and oxidative stress in many model systems. In this study, we aimed to investigate the possible protective effects of methanol extract of Cladonia rangiformis (CME) against the oxidative stress and the mutagenicity of AFB1 in vitro. Anti-genotoxic activity was evaluated by sister chromatid exchanges (SCEs) and micronucleus (MN) tests. The protective roles of CME against AFB1-induced oxidative stress on human peripheral lymphocytes culture was assessed by measuring following oxidative stress markers: superoxide dismutase (SOD), glutathione peroxidase (GPx), and malondialdehyde (MDA). The results suggested that CME decreased the oxidative effects of AFB1 significantly (p<0.05 or 0.001). It was also found that CME suppressed the mutagenic effects of AFB1at different concentrations in SCEs and MN tests. The data obtained in this study clearly show that CME is a potential anti-oxidative and anti-genotoxic agent against AFB1. © by PSP.
Keywords: Aflatoxin B 1; Anti-oxidant enzymes; Cladonia rangiformis; Genotoxicity